2000
DOI: 10.1159/000056295
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-Induced Increase in Isometric Tension of Smooth Muscle Is Mediated by Local Vagus Nerve in Human Bronchus

Abstract: Background: The vagus nerve is reported to play an important role in the regulation of airway responsiveness. Objective: In the present study, we investigated the role of the local vagus nerve in the changes in isometric tension of smooth muscle induced by histamine in the human airway. Methods: Eight human lung tissue specimens were obtained at thoracic surgery, and 24 bronchial smooth muscle strips were used for isometric tension recording. The changes in isometric tension were induced by histamine in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…111-113 The Some evidence for a role of non-neuronal acetylrelease of granulocyte-macrophage-colony stimucholine in the contractile response originates from lation factor (GM-CSF) leading to recruitment of Texperiments with histamine. The histamine-induced cells and eosinophils, is facilitated via stimulation of contractile response in human bronchi is increased nicotinic receptors from human bronchial epithelial by cholinesterase inhibition, 105 an effect which was cells. 112 In addition, under in vivo conditions, noncontributed to a simultaneous activation of vagal neuronal acetylcholine may directly stimulate the reneurons.…”
Section: Secretion (Absorption) Proliferationmentioning
confidence: 99%
“…111-113 The Some evidence for a role of non-neuronal acetylrelease of granulocyte-macrophage-colony stimucholine in the contractile response originates from lation factor (GM-CSF) leading to recruitment of Texperiments with histamine. The histamine-induced cells and eosinophils, is facilitated via stimulation of contractile response in human bronchi is increased nicotinic receptors from human bronchial epithelial by cholinesterase inhibition, 105 an effect which was cells. 112 In addition, under in vivo conditions, noncontributed to a simultaneous activation of vagal neuronal acetylcholine may directly stimulate the reneurons.…”
Section: Secretion (Absorption) Proliferationmentioning
confidence: 99%
“…Suppression of ACh-induced contraction to ASHMI is important, as ACh released from nerve terminals in murine and human studies has been shown to contribute to airway contractility and is thus physiologically relevant (2,42). Murine airways do not respond to histamine (18), and we observed very weak responses to serotonin (data not shown).…”
Section: Ashmi Dose-dependently Suppressed Ach-induced Tracheal Ring mentioning
confidence: 59%
“…There is previous evidence demonstrating PGE 2 release in response to ACh stimulation (9,32,38). The ratelimiting step of PGE 2 synthesis is arachidonic acid release via activation of phospholipase A 2 , which has been shown to have a calcium-dependent isoform-cytosolic phospholipase A 2 , in addition to calcium-independent isoforms (12).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenously administered histamine binds to H 1 receptors on the vagus nerve, inducing the release of acetylcholine, which binds to muscarinic receptors on airway smooth muscle causing constriction (15). Additionally, histamine binds directly to histamine receptors on airway smooth muscle cells, resulting in constriction.…”
Section: Discussionmentioning
confidence: 99%